Measurement of the electron-density profile in a discharge-ablated capillary waveguide. - Spence, D; Burnett, P; Hooker, S (Optical Society of America Inc., 1999)
We present the results of time-resolved interferometric measurements of the electron-density profile in a discharge-ablated capillary waveguide. We observe the development of a pronounced axial minimum in the electron-density profile with a relative depth of as much as 60% of the axial electron density. Such a profile is suitable for channeling high-intensity laser pulses.